Coordinated aggregated-based particle swarm optimisation algorithm for congestion management in restructured power market by placement and sizing of unified power flow controller - Hajforoosh, S.; Nabavi, S.; Masoum, Mohammad (Institution of Engineering and Technology, 2012)
This study presents a particle swarm optimisation (PSO)-based algorithm to perform congestion management by proper placement and sizing of one unified power flow controller (UPFC) device in a market-based power system. The algorithm uses quadratic smooth curves for generators’ costs. A typical load duration curve (LDC) is used to improve the accuracy of the model by incorporating the impacts of load variation on the optimisation problem. The proposed approach makes use of the PSO algorithm to allocate the near-optimal GenCos as well as the optimal location and size of UPFC whereas the Newton– Raphson solution minimises the mismatch of the power flow equations. Simulation results (without/with the line flow constraints, before and after the compensation) are used to analyse the impact of UPFC on the congestion levels of the reliability test system (RTS) 24-bus test system. Simulation results by the proposed PSO algorithm are also compared with solutions obtained by the conventional sequential quadratic programming (SQP) approach.